The Association Between the Gut Microbiota and Parkinson's Disease, a Meta-Analysis - Shen, Ting; Yue, Yumei; He, Tingting; Huang, Cong; Qu, Boyi; Lv, Wen; Lai, Hsin-Yi (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) patients were often observed with gastrointestinal symptoms, which preceded the onset of motor symptoms. Neuropathology of PD has also been found in the enteric nervous system. Many studies have reported significant PD-related alterations of gut microbiota. This meta-analysis was performed to evaluate the differences of gut microbiota between PD patients and healthy controls (HCs) across different geographical regions. We conducted a systematic online search for case-control studies detecting gut microbiota in PD patients and HCs. Mean difference (MD) and 95% confidence interval (95% CI) were calculated to access alterations in abundance of certain microbiota families in PD. Fifteen case-control studies were included in this meta-analysis study. Our results showed significant lower abundance levels of Prevotellaceae (MD = -0.37, 95% CI: -0.62 to -0.11), Faecalibacterium (MD = -0.41, 95% CI: -0.57 to -0.24), and Lachnospiraceae (MD = -0.34, 95% CI: -0.59 to -0.09) in PD patients compared to HCs. Significant higher abundance level of Bifidobacteriaceae (MD = 0.38, 95% CI: 0.12 to 0.63), Ruminococcaceae (MD = 0.58, 95% CI: 0.07 to 1.10), Verrucomicrobiaceae (MD = 0.45, 95% CI: 0.21 to 0.69), and Christensenellaceae (MD = 0.20, 95% CI: 0.07 to 0.34) was also found in PD patients. Thus, shared alterations of certain gut microbiota were detected in PD across different geographical regions. These PD-related gut microbiota dysbiosis might lead to impairment of short chain fatty acids producing process, lipid metabolism, immunoregulatory function and intestinal permeability, which contribute to the pathogenesis of PD.